New topographics. - Salvesen, Britt; Nordström, Alison; Exhibition. Rochester. George Eastman House international museum 2009-06,13; Exhibition. Tucson. Center for Creative Photography, University of Arizona 2009-02,19; Exhibition. Rotterdam. Nederlands Fotomuseum 2011-06,25 (Göttingen : Steidl, 2009)
New topographics / Britt Salvesen ## After new : thinking about new topographics from 1975 to the present / Alison Nordström ## Plates: Robert Adams ; Lewis Baltz ; Bernd and Hilla Becher ; Joe Deal ; Frank Gohlke ; Nicholas Nixon ; John Schott ; Stephen Shore ; Henry Wessel, Jr. ## Reproduction of the 1975 catalogue ## Checklist of the 1975 exhibition.
Rochester, 13.06.2009 - 27.11.2009
Tucson, 19.02.2009 - 10.01.2010
Rotterdam, 25.06.2011 - 11.09.2011
New topographics : photographs of a man-altered landscape (Rochester, International museum of photography, 1975)
boek
Keywords: Adams, Robert; Baltz, Lewis; Becher, Bernd; Becher, Hilla; Deal, Joe; Gohlke, Frank; Nixon, Nicholas; Schott, John; Shore, Stephen; Wessel, Henry